The Perfect Ruler in the Art and Literature of Medieval Bulgaria - Bakalova, Elka (Studia Ceranea, 2011)
The paper is an attempt to provide some information about the concept of the perfect ruler, as saved in the literature and the fine arts of the medieval Bulgaria, and which are related to the name of the king Ivan Alexander. The first part of the text is of theoretical character, showing how the ancient Greek literature presents the ideal ruler. The second one points out the characteristics of the portrayal of Ivan Alexander, as saved in both literary monuments (praises of the king in the Sofia psalter, so-called Pesnivec, 1337), and iconographical ones (a famous chronicle by Constantine Manasses, 1345–1346).